Nota sobre Abies pinsapo Clemente ex Boiss. y otras plantas andaluzas. About Abies pinsapo Clemente ex Boiss. and other Andalusian plants - Cabezudo, Baltasar; Pérez Latorre, Andrés V.; Casimiro-Soriguer Solanas, Federico; Gavira, Oscar; García Rojas, Juan A.; Pavón, Manuel (Acta Botanica Malacitana, 2010)
About Abies pinsapo Clemente ex Boiss. and other Andalusian plants About Abies pinsapo Clemente ex Boiss. and other Andalusian plants About Abies pinsapo Clemente ex Boiss. and other Andalusian plant . Palabras clave. Abies pinsapo, ? ora, Andalucía, España. Key words. Abies pinsapo, ? ora, Andalusia, Spain.